2018
DOI: 10.3390/met8060440
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Features of Microstructure in Maraging Steel Fabricated by Selective Laser Melting

Abstract: This study characterizes the microstructure and its associated crystallographic features of bulk maraging steels fabricated by selective laser melting (SLM) combined with a powder bed technique. The fabricated sample exhibited characteristic melt pools in which the regions had locally melted and rapidly solidified. A major part of these melt pools corresponded with the ferrite (α) matrix, which exhibited a lath martensite structure with a high density of dislocations. A number of fine retained austenite (γ) wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 28 publications
4
49
0
Order By: Relevance
“…This indicates that an almost fully hardened state is achievable with an aging temperature of 450 °C for maraging steel fabricated by SLM. It is worth noting that the aging temperature of 450 °C is lower by 30-40 °C in comparison with the aging temperature used for the maraging steel fabricated by the conventional manufacturing process and SLM [6,8].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This indicates that an almost fully hardened state is achievable with an aging temperature of 450 °C for maraging steel fabricated by SLM. It is worth noting that the aging temperature of 450 °C is lower by 30-40 °C in comparison with the aging temperature used for the maraging steel fabricated by the conventional manufacturing process and SLM [6,8].…”
Section: Resultsmentioning
confidence: 98%
“…Preliminary studies regarding the maraging steels produced by SLM showed that they have a unique microstructure and unique mechanical properties in comparison with those of the conventionally processed ones. For instance, Takata et al [6] investigated the microstructure of maraging steel produced by SLM and found that the alloy had a martensite phase in the as-built state due to an extremely fast cooling rate of up to 10 6 • C/s. It has been also shown that the maraging steel fabricated by SLM has finer structures compared to those of the conventional manufacturing methods due to a sufficiently fast cooling rate, resulting in higher strength [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the availability of tensile properties for AM fabricated maraging steel 300 for the primary build orientations (0 • , and 90 • ) is limited. Other significant work has been performed to-date in characterizing the microstructure [23,30,31,29,27,32], precipitation reactions [33,6], and austenite reversion behaviours [34,21,7,30] with several of these studies reporting similar microstructures in maraging steel 300 having been produced on a range of AM machines under varying process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Heat treatments were performed in a vertical tube furnace in argon atmosphere at 10 C/min heating rate. Based on the maraging steel's phase diagram 23,24 and recommended heat treatment procedures reported in literature, 25,26 age-hardening heat treatment was performed at 480 C for 3 h. Some samples underwent a solutionising treatment at 820 C for 1 h, with and without being followed by the designated age-hardening step. The notation of samples in different heat-treated states are as follows: 'AB' for as-built state, '3h480' for age-hardening heat treatment at 480 C for 3 h, '1h820' for solutionising at 820 C for 1 h and '1h820 + 3h480' for solutionising at 820 C for 1 h followed by age hardening at 480 C for 3 h. The chosen heat treatment for fatigue testing is 1h820 + 3h480 as will be seen in Section 3.…”
Section: Methodsmentioning
confidence: 99%